ECONOMIC EFFECTS OF OIL AND GAS PRODUCTION AND MANAGEMENT ON THE GHANAIAN ECONOMY - Acquah-Sam, Emmanuel (European Scientific Journal, ESJ, 2014)
This paper offers a systematic analysis of the likely economic effectsof oil and gas production and management on the Ghanaian economy. Thepaper has been motivated by the fact that some empirical literature reportthat natural resource endowment has not necessarily led to economicdevelopment in many countries. It is with this apprehension of a possiblenatural resource curse in Ghana, having discovered oil in commercialquantities that the economic effects of oil and gas production andmanagement on the Ghanaian economy are worth considering. The paperprovides basic descriptive analysis of the issues under consideration. Itconcludes that oil and gas production in Ghana does not provide a magicwand to transforming the economy of Ghana overnight, but the efficientmanagement and application of the revenues from the sale of the resourceswill provide keys to economic development of Ghana. Again, to ensureefficient use of the revenues from the resources, the revenues must be spenton specific projects of urgent national importance that could generate morerevenue in the long run and stand the test of time so as to help posterity tohave a better judgment of the use of the resources find.